2013
DOI: 10.1038/srep02585
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing Strawberry Spoilage via its Volatile Compounds Using Longpath Fourier Transform Infrared Spectroscopy

Abstract: The volatile compounds from fruits vary based on the spoilage stage. We used FTIR spectroscopy to analyze and to attempt to identify the spoilage process of strawberries. To enhance the sensitivity of the measuring system, we increased the optical pathlength by using multi-reflecting mirrors. The volatile compounds that were vaporized from strawberries in different spoilage stages were tested. We analyzed the spectra and found that the concentrations of esters, alcohols, ethylene, and similar compounds changed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 29 publications
0
24
0
Order By: Relevance
“…Measurements are performed at RT and very low humid- ity levels (8% RH) in order to determine true sensor response to alcohol vapours without interference of humidity. The target analyte concentration was set at 50 ppm, since it is typical concentration of alcohol vapour that can be detected during the food decay process [13], and tested with breath analyser [16]. Displayed responses reveal that printed SOZO sensor exhibits sensitivity to all tested alcohol vapours, and slight affinity to methanol gas.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Measurements are performed at RT and very low humid- ity levels (8% RH) in order to determine true sensor response to alcohol vapours without interference of humidity. The target analyte concentration was set at 50 ppm, since it is typical concentration of alcohol vapour that can be detected during the food decay process [13], and tested with breath analyser [16]. Displayed responses reveal that printed SOZO sensor exhibits sensitivity to all tested alcohol vapours, and slight affinity to methanol gas.…”
Section: Resultsmentioning
confidence: 99%
“…Cost-effective solutions to ambient monitoring, based on printed MO x nanomaterials, have strong impact on modern food production industry, which is today the fastest growing market for inkjet printing technology. Food decay process is often followed by the emission of volatile organic compounds (VOC) like alcohols [13], therefore a lot of attention is focused on the development of highly efficient sensors, operating at room temperature and having high sensitivity [14]. Smart packaging technology often requires sensor operation at different humidity levels, ranging from low to high, for mushrooms, maize, grains, spices and tomatoes [15].…”
Section: Introductionmentioning
confidence: 99%
“…We used a 1 L vacuum pump, FY-1H (ALUE Ltd., Shenyang, China), to exhaust gases from the gas cell. Our previous study demonstrated that the long-opticalpath FTIR system was much more sensitive than the common one (Dong et al, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…In previous works, we used multi-reflecting mirrors to increase the optical path of a common FTIR (Fourier transform infrared spectroscopy) system, studied the volatiles released from grapes and strawberries and observed the spectral characteristics corresponding to alcohols, esters, etc. (Dong et al, 2013(Dong et al, , 2014a(Dong et al, , 2014bWenzhong et al, 2013). The results revealed that it is possible to classify fruit spoilage stages via their volatiles using infrared spectroscopy.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation